Isolation of Phosphinoimino‐2‐imidazoline. Issue 22 (9th September 2016) - Chong, Che Chang; Ganguly, Rakesh; Li, Yongxin; Kinjo, Rei
Abstract : The phosphinoimino‐2‐imidazoline4 was synthesized by a salt elimination reaction between LiNIPr [NIPr = 1, 3‐bis(2, 6‐(diisopropylphenyl)imidazolin‐2‐ylidenamino)] and 2‐chloro‐1, 3, 2‐diazaphospholene. DFT study revealed that the HOMO of4 involves the lone pair orbitals on the P atom and the N atom at the exocyclic P–N bond. Compound4 displays selectivity in coordinating to acids. Thus, the N atom at the exocyclic P–N bond coordinates to a hard acid (HCl) which eventually led to the cleavage of the P–N bond, while the central P atom forms a dative bond with a soft Lewis acid, BH3 . Abstract :